MR-Guided Prostate Interventions. Issue 3 (June 2018) - Woodrum, David A.; Gorny, Krzysztof R.; Mynderse, Lance A.
Abstract : Abstract: Prostate cancer is the most commonly diagnosed noncutaneous cancer and second leading cause of death in men. Many patients with clinically organ-confined prostate cancer undergo definitive treatment of the whole gland, including radical prostatectomy, radiation therapy, and cryosurgery. Active surveillance is a growing alternative option for patients with documented low-volume and low-grade prostate cancer. However, many patients are wanting a less morbid focal treatment alternative. With recent advances in software and hardware of magnetic resonance imaging (MRI), multiparametric MRI of the prostate has been shown to improve the accuracy in detecting and characterizing clinically significant prostate cancer. Targeted biopsy is increasingly utilized to improve the yield of MR detected, clinically significant prostate cancer and to decrease in detection of indolent prostate cancer. MR-guided targeted biopsy techniques include cognitive MR fusion transrectal ultrasound (TRUS) biopsy, in-bore transrectal targeted biopsy using robotic transrectal device, and in-bore direct MR-guided transperineal biopsy with a software based transperineal grid template. In addition, advances in MR-compatible thermal ablation technology allow accurate focal or regional delivery of thermal ablative energy to the biopsy-proved, MRI-detected tumor. MR-guided ablative treatment options include cryoablation, laser ablation, and high-intensity focused ultrasound with real-time or near simultaneous monitoring of the ablation zone. We present a contemporary review of MR-guided techniques for prostatic interventions.